Restrained Weakly Connected 2-Domination in the Vertex and Edge Coronas of Graphs - Militante, Mae P.; Eballe, Rolito G. (Communications in Mathematics and Applications, 2023)
In this paper, we explore the concept of restrained weakly connected 2-domination in the vertex and edge coronas of graphs. In particular, we characterize the restrained weakly connected 2-dominating sets in the vertex and edge coronas of two graphs and obtain the corresponding restrained weakly connected 2-domination numbers of these graphs.